Arterial stiffness is associated with oxidative stress and endothelial activation among persons with treated HIV in Zambia - Theresa Chikopela (AOSIS, 2021)
Background: Cardiovascular disease (CVD) prevalence is rising among persons with HIV (PLWH) in sub-Saharan Africa. Oxidative stress and endothelial activation, resulting in reduced vascular compliance, are contributors to CVD risk. However, there is a paucity of vascular health data in this population.